Предмет: Алгебра,
автор: Littlequeen
Упростить выражение:
(6х-х²)²-х²(х-1)(х+1)+6х(3+2х²)
Ответы
Автор ответа:
0
( 6x - x²)² - x²( x - 1)( x + 1) + 6x( 3 + 2x²) = 36x² - 12x³ + x⁴ - x²( x² - 1) + 18x+12x³ =
= 36x² + x⁴ + 18x - x⁴ + x² = 37x² + 18x = x( 37x + 18)
= 36x² + x⁴ + 18x - x⁴ + x² = 37x² + 18x = x( 37x + 18)
Похожие вопросы
Предмет: Английский язык,
автор: Человек999999
Предмет: История,
автор: durackov659
Предмет: Химия,
автор: timurkostin769
Предмет: Алгебра,
автор: obik
Предмет: Математика,
автор: ОльчикОфигеная